Maqasid al-Syari’ah dalam Penegakkan Hukum Lalu Lintas di Indonesia - Busriyanti, Busriyanti (Institut Agama Islam Negeri Curup, 2021)
The high number of traffic accidents in Indonesia occurred because the traffic law enforcement does not run optimally. This paper tried to explore the rules regarding the traffic that have been contained in the form of Law no. 22 of 2009 concerning Road Traffic and Transportation and other regulations from an Islamic legal point of view, especially through the study of maqashid al-shari’ah. The maqashid al-shari’ah approach is used as an approach because maqashid explains the wisdom behind the rules of Islamic shari’ah. The maqashid approach used by the author in this paper is the maqashid classification used by Jamaluddin al-Athiya which divided maqashid into four domains, they are maqashid al-shari’ah in the individual realm, maqashid al-shari’ah in the family realm, maqashid al-shari’ah in the realm of the ummah and maqashid al-shari’ah in the realm of humanity. It can be concluded that law enforcement in traffic matters in Indonesia is in line with the objectives of maqashid al-shari’ah relating to maqashid al-ummah, especially in terms of maintaining stability, security, and justice. Regulations concerning traffic order are matters of the nature of dharuriyyat at this time because the existence of rules regarding traffic will protect matters that are essential in human life, they are religion, soul, mind, descent, and property.